Drug-loaded poly(d, l-lactide-co-glycolide) microspheres as treatment for allergic contact dermatitis in mice model. (September 2017) - Shi, Chen; Liu, Ping; He, Yu; Liu, Yongwei; Feng, Xiaobo; Fu, Dehao
Allergic contact dermatitis is a common skin disease and the current treatment always along with frequent medication and side effect. In this research, poly(d, l -lactide- co -glycolide) microspheres encapsulating tacrolimus are first employed as a therapy of allergic contact dermatitis in mice model by subcutaneous injection. Allergic contact dermatitis is successfully induced in BALB/c mice by repeated painting of dinitrofluorobenzene on mice ear. Tacrolimus is efficiently encapsulated into poly(d, l -lactide- co -glycolide) microspheres by emulsion evaporation method, and then the microspheres are subcutaneously injected into dermatitis-suffered BALB/c mice. We find that the dermatitis mice treated with tacrolimus-loaded microspheres get a sustained suppression on ear swelling, dermatitis index, inflammatory cell accumulation, and serum immunoglobulin E concentration. The curative effect of tacrolimus-loaded microspheres is similar to daily tacrolimus injection and is even better in the inhibition of ear swelling. Dermatitis mice treated with blank microspheres get no curative effect during the whole experiment. The data suggest that subcutaneous injection of drug-loaded microspheres could be a potential candidate for the management of allergic contact dermatitis.